Population adherence to the use of masks for the prevention and control of COVID-19: integrative literature review (Research, Society and Development, 2022)
The objective was to analyze the evidence available in the literature on the adherence of the general population over 18 years of age to the use of masks for the prevention and control of COVID-19. This integrative review was registered in the Open Science Framework prior to carrying out the searches. The search was conducted on February 19, 2021, in the following databases: National Library of Medicine, Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Literature in Health Sciences, Embase and Web of Science. A total of 17 studies were selected to integrate this review. Being 16 (94.2%) with a quantitative approach and one (5.8%) qualitative, mostly published in English in 16 different journals in the health area. The evidence available in the literature on the population's adherence to the use of masks for the prevention and control of COVID-19, showed a difference in the levels of compliance with specific preventive measures against COVID-19 related to variables such as the compulsory use of masks and , personal, environmental and cultural factors.